Evaluation of solid waste management system in ‘X’ hospital, Cilegon city, Banten - Linardita Ferial; Budi Rahayu Kosasih (Fakultas Kedokteran Universitas Gadjah Mada, 2018)
Health service activities by the hospital produce a waste of any activity in the form of medical activities and non-medical activities. The purpose of this research is to analyze the solid waste management system in 'X' Hospital, Cilegon City, Banten. The result showed that the source of solid waste generated were classified into 2 types, namely 2% of medical waste and 98% non medical, where the waste treatment process included sorting, characteristic wastage, transporting garbage to TPS, weighing, temporary storage and transportation. The method of handling solid, B3 and domestic solid waste in 'X' Hospital is done in each unit which is sorting according to its characteristic, but still finding the placement of waste which is not in accordance with its characteristic and solid waste processing process is not done by the hospital but given to a third party. Therefore, it can be concluded that the effort to evaluate the solid waste management of 'X' Hospital must refer to the Decree of the Minister of Health of the Republic of Indonesia Number 1204 / Menkes/ SK / X / 2004 on Hospital Health Requirements and need to improve supervision and good cooperation with nurses and janitors in the separation of medical and non-medical waste.